TIPOLOGI STRATEGI PENAMBAHAN PETER NEWMARK DALAM PENERJEMAHAN KITAB UṢŪL AL-FIQH SYARḤ AL-WARAQĀT - Mohammad Nasih Al Hashas (Sunan Kalijaga State Islamic University Yogyakarta, 2025)
The addition of editorials in translations is often found in Islamic religious books, especially in the discipline of Uṣūl al-Fiqh. One example is the Syarḥ al-Waraqāt by Imām Ḥaramain, translated by Mujiburrahman. This book is written in the ījāz style (few words but rich in meaning), so it requires additional explanations to make its meaning easier for readers to understand. This study aims to describe the forms of addition strategies in the translation of the Syarḥ al-Waraqāt book and explain the process of its occurrence in the context of Arabic-Indonesian translation. This study uses a qualitative descriptive approach with documentation methods and note-taking techniques. The results show that the translation process is in line with Peter Newmark's translation strategy theory. Two forms of addition strategies were found: additions made based on considerations of language structure, and additions made based on semantic considerations to clarify or enrich the meaning of the text. The addition process is carried out in three ways: inserting additions directly into the text, writing them in brackets, or placing them in footnotes. These three methods reflect the application of amplification and description techniques in the translation of Islamic books.